Pengaruh Rasio Keuangan, Sales Growth dan Ukuran Perusahaan terhadap Financial Distress pada Sektor Industri Barang Konsumsi yang Terdaftar di BEI 2017-2020 - Muzharoatiningsih Muzharoatiningsih; Ulil Hartono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Financial distress is the initial condition of the company before going bankrupt. This means that it is important to prevent financial distress to anticipate the occurrence of bankruptcy. This study aims to determine the effect of financial ratios and company size on financial distress. The independent variables used in this study consist of return on assets, current ratio, debt to assets ratio, sales growth, and company size. The type of research chosen is causal associative. The population in this study is a company listed on the Indonesia Stock Exchange in the consumer goods industry sector for the 2017-2020 period. The sampling technique used in this research is purposive sampling which produces 12 companies as samples in the consumer goods industry. The data were analyzed using logistic regression and calculated using SPSS version 26 software. The result showed that the return on asset ratio had a negative significance value on financial distress. While other variables, namely the current ratio, debt to assets ratio, sales growth, firm size have no significant effect on financial difficulties. In this regard, more attention is needed when the return on assets decreases in value to avoid financial distress conditions.